Analysis of Buying Decision Variables for Subsidized Residence (A Case Study at Housing Banyu Herang Regency Garut) - Alam, Bayu Purnama; Larso, Dwi (Journal of Business and Management, 2016)
Abstract- The main themes  of this  research on the "location  housing, ease of getting loans, income, house prices, facility and public facility and legal aspect of the home purchase decision in Banyu Herang Garut Regency". The method used in this research is quantitative research methods to approach the problem formulation descriptive and verification. In this study, the data used is primary data. The statistical test used in this study multiple linear regression method. Results of research are based on a statistical calculation results of multiple regression analysis, it can be concluded that, partially, the variable housing Locating affect the Home Purchase decision, and for variable Ease of Getting Loans no effect on the Home Purchase decision, variable income does not affect the Home Purchase decision and also variable House Prices affect the Home Purchase decision, Facilities variable does not affect the Home Purchase final decision and Legal Aspect variables affect the Home Purchase decision. For analysis together simultaneously variables simultaneously housing Locating variable (X1), Ease of getting loans (X2) Income (X3) House prices (X4) Facilites (X5), and Legal aspect (X6) effect on variable Home Purchase Decision (Y) with a total effect of 92.5%, while the remaining 7.5% is influenced by other factors not observed. Keywords: Locating housing, Easy of getting loans, Income, House prices, Facility and public facility and Legal aspect of the Home Purchase decision.